2012 IEEE Globecom Workshops 2012
DOI: 10.1109/glocomw.2012.6477622
|View full text |Cite
|
Sign up to set email alerts
|

Available Bandwidth Probing for path selection in heterogeneous home Networks

Abstract: The time-varying capacity links, such as wireless links and power line communication (PLC) links, which are integrated to emergent connectivity devices of Home Networks (HNs) require QoS mechanisms to protect sensitive and critical HN flows. In this paper, we couple the "Iperf in lightweight TCP mode" probing technique (developed in a previous work to estimate available bandwidth) with the path selection procedure of the "Inter-MAC" software (which was derived from the European OMEGA project, to handle heterog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 3 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…However, it does not take into account the fact that users do not have dedicated network resources when using wireless technologies. In general, Olvera-Irigoyen et al have shown that determining the actual available bandwidth on the links has a big impact on the results of load balancing the flows in a (wireless) network, in particular with time-varying capacity Wi-Fi and Power line communication (PLC) links [20]. Recent load balancing solutions for LANs focus also on energy optimization by, for instance, selecting the most energy efficient link while still providing a good QoS [21,22].…”
Section: Load Balancing In Heterogeneous Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it does not take into account the fact that users do not have dedicated network resources when using wireless technologies. In general, Olvera-Irigoyen et al have shown that determining the actual available bandwidth on the links has a big impact on the results of load balancing the flows in a (wireless) network, in particular with time-varying capacity Wi-Fi and Power line communication (PLC) links [20]. Recent load balancing solutions for LANs focus also on energy optimization by, for instance, selecting the most energy efficient link while still providing a good QoS [21,22].…”
Section: Load Balancing In Heterogeneous Networkmentioning
confidence: 99%
“…A key element for determining an optimal configuration is to have an accurate overview of the available bandwidth per BSS. The big impact of determining the actual available bandwidth of wireless links on the results of load balancing approaches has been shown in literature [20,32]. The actual bandwidth of wireless technologies depends on several parameters such as the theoretical physical bandwidth, the configuration of APs, the interference of other devices within or outside the network, and the number of traffic in the network.…”
Section: Parameter Estimationmentioning
confidence: 99%
“…The proposed algorithm is based on the Wardrop equilibrium and does not take into account the fact that users do not have dedicated network resources when using wireless technologies. In general, it was shown that determining the actual available bandwidth on the links has a big impact on the results of distributing the flows [20]. Recent load balancing solutions focus also on energy optimization.…”
Section: B Load Balancing In Heterogeneous Local Area Network (Lans)mentioning
confidence: 99%